Anger and indigenous men : understanding and responding to violent behaviour - Day, Andrew; Nakata, Martin N; Howells, Kevin (Leichhardt, N.S.W. : Federation Press, 2008)
'This book is for social work and criminal justice practitioners who wish to develop culturally appropriate and effective programs for reducing anger-related violence perpetrated by indigenous men. It places cultural context at the heart of any intervention, broadening the focus from problematic behaviour to a more holistic notion of well-being. The book is structured in three parts. Part 1 explores indigenous perspectives on anger and violence, on both sociological and psychological levels. The different views presented show there is no single cause but provide contexts for understanding an individuals anger. Part 2 outlines methodologies and processes for collecting meaningful data on anger and indigenous men. Part 3 presents ideas for developing and delivering anger management programs that meet the needs of indigenous men: how to adapt existing programs in culturally appropriate ways, specific needs of the staff delivering the programs, a pedagogical framework and sample session plans, and future directions for program development and evaluation. The contributors include psychologists, counsellors, educationalists and academics from both indigenous and non-indigenous backgrounds.'--Provided by publisher
Includes index
Bibliography: p. [259] - 275
Keywords: Aboriginal Australians -- Psychology; Aboriginal Australians -- Mental health; Aboriginal Australians -- Rehabilitation; Family violence -- Australia -- Prevention; Anger; Conflict management